Auxiliary Metabolic Gene Functions in Pelagic and Benthic Viruses of the Baltic Sea - Heyerhoff, Benedikt; Engelen, Bert; Bunse, Carina (Frontiers in Microbiology, 2022)
Marine microbial communities are facing various ecosystem fluctuations (e.g. temperature, organic matter concentration, salinity or redox regimes) and thus have to be highly adaptive. This might be supported by the acquisition of auxiliary metabolic genes (AMGs) originating from virus infections. Marine bacteriophages frequently contain AMGs, which allow them to augment their host’s metabolism or enhance virus fitness. These genes encode for the same metabolic functions as their highly similar host homologues. Here, we analyzed the diversity, distribution, and composition of marine viruses, focusing on AMGs to identify their putative ecologic role. We analyzed viruses and assemblies of 212 publicly available metagenomes obtained from sediment and water samples across the Baltic Sea. In general, the virus composition in both compartments differed compositionally. While the predominant viral lifestyle was found to be lytic, lysogeny was more prevalent in sediments than in the pelagic samples. The highest proportion of AMGs were identified in genomes of the Myoviridae. Overall, the most abundantly occurring AMGs encoded for functions that protect viruses from degradation by their hosts, such as methylases. Additionally, some detected AMGs are known to be involved in photosynthesis, 7-cyano7-deazaguanine synthesis and cobalamin biosynthesis among other functions. Several AMGs that were identified in this study were previously detected in a large-scale analysis including metagenomes from various origins, i.e. different marine sites, wastewater and the human gut. This supports the theory of globally conserved core AMGs that are spread over virus genomes, regardless of host or environment.